2018
DOI: 10.1051/matecconf/201815705014
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and bending test of carbon/epoxy and carbon/geopolymer composites after temperature conditioning

Abstract: Composites with epoxy matrix cannot be used in high temperature, while geopolymer matrix excel in high temperature resistance. First, prismatic specimens were subjected to conditioning temperature. Second, the tensile and bending test were performed at room temperature. This paper present comparison of mechanical properties of carbon/epoxy and carbon/geopolymer composites. Numerical simulations of tensile and bendidng tests were performed in finite element system Abaqus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 3 publications
2
15
0
Order By: Relevance
“…For 0.0% alumina, the three treatments values of modulus of elasticity are 2197. 29 Table 4 summarizes the ANOVA statistical approach of modulus of elasticity values for three the treatments of 0.0%, 1.5%, 3.0%, and 4.5% alumina nanoparticles. A 0.0% alumina containing medium density fiberboard has a mean value of 2332.087 N/mm 2 and a variance of 13,748.06.…”
Section: Statistical Analysis Of the Mechanical And Physical Propertimentioning
confidence: 99%
See 2 more Smart Citations
“…For 0.0% alumina, the three treatments values of modulus of elasticity are 2197. 29 Table 4 summarizes the ANOVA statistical approach of modulus of elasticity values for three the treatments of 0.0%, 1.5%, 3.0%, and 4.5% alumina nanoparticles. A 0.0% alumina containing medium density fiberboard has a mean value of 2332.087 N/mm 2 and a variance of 13,748.06.…”
Section: Statistical Analysis Of the Mechanical And Physical Propertimentioning
confidence: 99%
“…Yan et al [22], Kovarik et al [19], and Bernal et al [27], studied the mechanical properties of samples cured at high-temperature and laboratory temperature heat treatment. Some properties namely compressive strength [19,23,27], impact resistance [24,25], Young's modulus [20,22,25], tensile properties [28,29], and flexural strength [19][20][21][22]25], were inspected on composites with alkali-activated aluminosilicates. It was found that the properties of composites with alkali-activated aluminosilicates depend on cure conditions of composites, type of fiber reinforcement, composition of alkali-activated aluminosilicates and number of layers of fiber reinforcement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical properties were studied on samples cured at laboratory temperature and even after high-temperature heat treatment [6,14,21]. Commonly, compressive strength [14,17,21], flexural strength [6,14,15,16,19], Young’s modulus [6,15,19], tensile properties [22,23], and impact resistance [18,19] were investigated on composites with A-matrix. The properties of A-matrix composites depended on the type of fiber reinforcement, number of layers of fiber reinforcement, composition of A-matrix, A-matrix/fiber reinforcement weight ratio, and cure conditions of composites.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of A-matrix composites depended on the type of fiber reinforcement, number of layers of fiber reinforcement, composition of A-matrix, A-matrix/fiber reinforcement weight ratio, and cure conditions of composites. Krystek et al [23] prepared composites with A-matrix and carbon fabric. The prepared samples reached a tensile strength up to 265 MPa.…”
Section: Introductionmentioning
confidence: 99%